A double-blind intervention trial in healthy women demonstrates the beneficial impact on Bifidobacterium with low dosages of prebiotic galacto-oligosaccharides - Looijesteijn, Ellen; Schoemaker, Marieke H.; van den Belt, Maartje; Hester, Eric R.; Kortman, Guus A. M.; Viskaal-van Dongen, Mirre; Nauta, Arjen (Frontiers in Nutrition, 2024)
Introduction: Galacto-oligosaccharides (GOS) are well-substantiated prebiotic substrates. Multiple studies have demonstrated a positive impact of GOS on gut microbiota composition and activity, sofar mainly related to Bifidobacterium. However, data on the beneficial impact at lower dosages in a healthy female population are limited. The primary aim of the current study was to reveal the effect of low dosages (1.3 and 2.0g) of GOS on fecal Bifidobacterium abundance in healthy women. Other outcomes included the effect of low dosage of GOS on overall fecal microbiota composition and on self-perceived GI comfort, sleep quality and mental wellbeing.Method: Eighty-eight healthy women (42-70 y, BMI 18.7-30 kg/m 2 ) were included in this randomized, parallel, double-blind study of 6 weeks. The participants were stratified for fiber intake, BMI and age and randomized to consume either 1.3 or 2.0g of GOS per day for 3 weeks after a control period of 3 weeks without any intervention. Fecal samples were collected for shotgun metagenomics sequencing at the start (t=-3) and end (t=0) of the control period and at the end of the intervention period (t=3). Self-perceived gut comfort, sleep quality, and mental wellbeing were assessed weekly. Hierarchical clustering of principal components was applied to data collected from study participants.The relative abundance of Bifidobacterium in feces increased significantly after 3 weeks of daily consumption of both 1.3g (p<0.01) and 2.0g GOS (p<0.01). This was accompanied by a significant shift in the overall microbiota composition for the dosage of 2.0g GOS (p<0.01). Participants that showed a larger increase in Bifidobacterium in the intervention period compared to the change in Bifidobacterium in the control period, defined as responders, showed a significant overall difference in initial fecal microbiota composition as compared to non-responders (p=0.04) and a trend towards lower baseline levels of Bifidobacterium in responders (p=0.10).Daily consumption of a low dose of GOS can lead to an increase in the relative abundance of Bifidobacterium in feces of healthy women. Additionally, with 2.0g GOS, the enrichment of Bifidobacterium is accompanied with a shift in the overall microbiota composition.The study was registered at clinicaltrials.gov, identifier NCT05762965.